Overview of recent advancement in globalization and outsourcing initiatives in manufacturing systems - Ikumapayi, O.M.; Oyinbo, S.T.; Akinlabi, E.T.; Madushele, N. (Materials today : proceedings, 2020)
This study surveys the recent advancement in globalization and outsourcing technology employed in manufacturing systems which are automation, virtual reality, agile manufacturing, internet of things, flexible manufacturing systems, continue manufacturing system, automotive, computer numerical control system, 3D printing, nuclear reactors as well as composite welding, etc. The survey shows that this advancement reduced operational costs at the same time maximize company’s profits. It is worth mentioning that outsourcing and globalization differ from one manufacturing company to the other and this has propelled cross border trade as well as exchange of ideas among the international companies. By so doing, international bonding amongst the interaction companies has been established and their communication style has become cordial. It has been noted that outsourcing staff has gained technical and managerial skills thereby become more competent and flexible in dealing with business whereas agile manufacturing plays a very important role in how a manufacturer responds to the shift in customer demand. In this survey, it was established that virtual reality enables the interrelation between the computer as well as human operator which activates manipulation and visualization of complex data. In the case of flexible manufacturing system, different machines can be rearranged for different operations in a single role and generate products in a short possible time whereas, continuous manufacturing enables the production line to take place continuously by the use of highly skilled personnel.